2014
DOI: 10.1557/jmr.2014.24
|View full text |Cite
|
Sign up to set email alerts
|

On acquiring true stress–strain curves for sheet specimens using tensile test and FE analysis based on a local necking criterion

Abstract: In this study, we obtain true stress-strain (SS) curves for a sheet specimen under consideration of local necking and material anisotropy. We first extract the SS curve up to the diffuse necking point from the tensile test load-displacement data. The curve's part after the onset of diffuse necking is extrapolated by the weighted-average method proposed by Ling [Y. Ling, AMP J. Technol. 5, 37-48 (1996)]. Initiation of local necking is predicted by means of the minor-to-major strain ratio in the specimen's cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…A standard procedure for the determination of trues stress and the true strain was used: = (1 + ), = (1 + ), where and are true stress and true strain, respectively, and are engineering stress and engineering strain, respectively. This approach is correct if the specimen deforms uniformly without neck formation [30,31]. In situ observations of the specimens during high-temperature tensile deformation showed that at elongations lower than 300% (~1.4), specimens deformed uniformly.…”
Section: Resultsmentioning
confidence: 99%
“…A standard procedure for the determination of trues stress and the true strain was used: = (1 + ), = (1 + ), where and are true stress and true strain, respectively, and are engineering stress and engineering strain, respectively. This approach is correct if the specimen deforms uniformly without neck formation [30,31]. In situ observations of the specimens during high-temperature tensile deformation showed that at elongations lower than 300% (~1.4), specimens deformed uniformly.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to necking, the specimen is in a uniaxial stress state, whereas after necking, it is in a tri‐axial stress state. Since the flow stress associated with a tri‐axial stress state is larger than that associated with a uniaxial stress state, an appropriate correction is required .…”
Section: Mechanical Behavior Of Mppomentioning
confidence: 99%
“…Y 11 ). Anisotropy ratios and coefficients for zircaloy-4 and zirlo were previously determined from tensile tests ( Table 2) [20]. Chemical composition of zircaloy-4, which the paper is mainly concerned with and for which combined hardening coefficients are obtained eventually, is in accordance with ASTM: B350/B350M-11; main alloying elements are Sn (1.30 wt.%), Fe (0.22 wt.%), Cr (0.12 wt.%) and O (0.12 wt.%).…”
Section: Finite Element Model For Simple Shear Test and Materials Propmentioning
confidence: 99%
“…Anisotropy ratios and coefficients for Hill 48 yield criterion for zircaloy-4 and zirlo from tensile tests, as in[20].Fig. 4.…”
mentioning
confidence: 99%